Evaluation of Some Oxidants and Antioxidants Parameters in Iraqi Females with Celiac Disease - Farah Kamal Khalf; Nada A. Kadhim (Ibn Al-Haitham Journal for Pure and Applied Sciences)
An inherited tendency is necessary for the manifestation of celiac disease (CD), an autoimmune, gluten-sensitive, inflammatory disorder of the small intestine. Gluten, a storage protein in cereals, causes CD. An increase in oxidant compound generation, surpassing the capacity of the endogenous antioxidant system, causes oxidative stress (OS). This study aims to evaluate some oxidants and antioxidants factors in Iraqi females with CD. This hospital-based cross-sectional study at Baghdad Educational Hospital in Baghdad, Iraq, involved 100 female participants of reproductive age. Tests have been measured, such as total oxidants (TOS), total antioxidants (TAS), malondialdehyde (MDA), catalase (CAT), nitric oxide (NO), total protein (TP), and Hb. The results of the present study showed that 72 of the female patients had Hb less than 12, whereas 28 had Hb equal to or greater than 12. The anemic patient group had elevated OS indices and a low TAS. Because of the damaged small intestine, CD patients experienced an imbalance between oxidant and antioxidant parameters, which was increased with anemia.